2017
DOI: 10.5230/jgc.2017.17.e40
|View full text |Cite
|
Sign up to set email alerts
|

Laparoscopic Reinforcement Suture (LARS) on Staple Line of Duodenal Stump Using Barbed Suture in Laparoscopic Gastrectomy for Gastric Cancer: a Prospective Single Arm Phase II Study

Abstract: PurposeLaparoscopic gastrectomy is accepted as a standard treatment for patients with early gastric cancer in Korea, Japan, and China. However, duodenal stump leakage remains a fatal complication after gastrectomy. We conducted a prospective phase II study to evaluate the safety of the new technique of laparoscopic reinforcement suture (LARS) on the duodenal stump.Materials and MethodsThe estimated number of patients required for this study was 100 for a period of 18 months. Inclusion criteria were histologica… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

0
17
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 15 publications
(17 citation statements)
references
References 27 publications
0
17
0
Order By: Relevance
“…Some studies underlined the importance of suture line reinforcement in DSF prevention [2]. In a recent prospective phase II study, Kim et al highlighted DSF absence in 100 patients undergoing laparoscopic reinforcement suture (LARS) with barbed suture during laparoscopic gastrectomy for gastric cancer [24]. Other authors suggested application of coated sutures, fibrin glues or resorbable reinforcements [2].…”
Section: Discussionmentioning
confidence: 99%
“…Some studies underlined the importance of suture line reinforcement in DSF prevention [2]. In a recent prospective phase II study, Kim et al highlighted DSF absence in 100 patients undergoing laparoscopic reinforcement suture (LARS) with barbed suture during laparoscopic gastrectomy for gastric cancer [24]. Other authors suggested application of coated sutures, fibrin glues or resorbable reinforcements [2].…”
Section: Discussionmentioning
confidence: 99%
“…In both groups, the mean numbers of LNs harvested were far exceeded the 15 LNs required by the guidelines [ 13 , 14 ] and the average numbers of LNs in the greater curvature and lesser curvature were (12.18 ± 6.55 vs. 13.62 ± 8.09, p = 0.444) and (19.55 ± 7.40 vs. 17.98 ± 8.31, p = 0.365) in SD and rEME group, respectively. The quality of lymph node dissection can be maintained in comparison with that in previous reports whether from the West or the East [ 15 , 25 27 ] which suggests that this procedure can provide pathologically reliable lymphadenectomy. By the anatomical sharp dissection tracing the reasonable plane and space, the average blood loss and duration of surgery were also similar to other studies from big centers [ 22 , 25 ].…”
Section: Discussionmentioning
confidence: 58%
“…The quality of lymph node dissection can be maintained in comparison with that in previous reports whether from the West or the East [ 15 , 25 27 ] which suggests that this procedure can provide pathologically reliable lymphadenectomy. By the anatomical sharp dissection tracing the reasonable plane and space, the average blood loss and duration of surgery were also similar to other studies from big centers [ 22 , 25 ]. Postoperative complications developed in seven patients (15.55%), including Clavien–Dindo classification of IIIb in two.…”
Section: Discussionmentioning
confidence: 58%
“…Following a review and technical improvement, the stump was embedded, which allowed for a marked reduction in leakage from the duodenal stump. 18,19 . Interestingly, all duodenal stump leakage took place after total gastrectomy in our institution, no duodenal stump leakage occurred after distal gastrectomy, which may relate to some patients with distal gastrectomy using of a double cannula for preventive irrigation.…”
Section: Discussionmentioning
confidence: 99%